DEVELOPMENT OF BUDDHIST SPIRITUAL LEADERSHIP INDICATORS OF BUDDHIST UNIVERSITY ADMINISTRATORS IN THAILAND - Srinonyang, Pradit; Podapol, Chakkrit; Sod-ium, Pim-on (Journal of Social Science and Cultural, 2024)
This article aimed to study the components and indicators of spiritual leadership based on Buddhist principles, examine the consistency of the structural equation model of spiritual leadership indicators based on Buddhist principles of administrators of Buddhist universities in Thailand with empirical data, and explore the approaches for developing spiritual leadership according to Buddhist principles. The research employed a mixed-method approach. The key informants included eight individuals comprising monks, professors, and academics holding academic positions. The sample group consisted of 550 professors and staff from Mahamakut Buddhist University and Mahachulalongkornrajavidyalaya University, selected through stratified random sampling. The research instruments included 1) Semi-structured interviews, 2) Questionnaires, and 3) In-depth interviews. Data were analyzed using a statistical software package, along with content analysis and descriptive analysis. The research findings revealed that the components and indicators of spiritual leadership based on Buddhist principles consisted of five main components, 19 sub-components, and 86 indicators. The results of the consistency test of the structural equation model of spiritual leadership indicators based on Buddhist principles of the administrators of Buddhist universities in Thailand aligned with the empirical data, with Chi-Square = 80.31, P-value = 0.06968, df = 63, Relative Chi-Square = 1.274, Goodness-of-Fit Index = 0.984, Adjusted Goodness-of-Fit Index = 0.952, and Root Mean Square Error of Approximation = 0.023. Regarding the development of spiritual leadership based on Buddhist principles, administrators should receive training on organizational goals and management, have clear plans and evaluation criteria, provide guidance and listen to feedback, be truthful in words and actions, manage emotions, and offer assistance when problems arise.